Allergic contact dermatitis in psoriasis. (1st February 2019) - Claßen, A.; Buhl, T.; Schubert, S.; Worm, M.; Bauer, A.; Geier, J.; Molin, S.; ,
Summary: Recent research suggests that people with the skin disease psoriasis may be at less risk of developing contact dermatitis, which is an eczema‐like reaction in response to the skin coming into contact with an irritant (irritant contact dermatitis) or allergen (allergic contact dermatitis, or ACD). This study looked at the prevalence of ACD specifically, in 2387 people with psoriasis who had been patch tested, compared to 161 981 patch tested people without psoriasis. Patch testing is used to find out which potential allergens cause a skin reaction in a person. Overall, 25.2% of the people with psoriasis and 38.9% of people without psoriasis showed at least one reaction to the allergens used in patch testing. These findings revealed a significantly lower overall risk for ACD in individuals with psoriasis. Taken together, psoriasis and contact dermatitis both involve complex processes of the body's immune system that make it difficult to understand what happens when both occur together. This research helps further our understanding on the topic.